DoE‐Driven Development of an Organocatalytic Enantioselective Addition of Acetaldehyde to Nitrostyrenes in Water. Issue 24 (22nd March 2022) - Nori, Valeria; Sinibaldi, Arianna; Giorgianni, Giuliana; Pesciaioli, Fabio; Di Donato, Francesca; Cocco, Emanuele; Biancolillo, Alessandra; Landa, Aitor; Carlone, Armando
Abstract: The development of an enantioselective enamine‐catalysed addition of masked acetaldehyde to nitroalkenes via a rational approach helped to move away from the use of chloroform. The presented research allows the use of water as a reaction medium, therefore improving the industrial relevance of a protocol to access very important pharmaceutical intermediates. Critical to the success is the use of chemometrics‐assisted 'Design of Experiments' (DoE) optimisation during the development of the presented new synthetic approach, which allows to investigate the chemical space in a rational way. Abstract : It's in the design : Moving from organic solvents to water is not always an easy task, especially when a lot of variables need to be screened. The development of an enantioselective enamine‐catalysed Michael addition of acetaldehyde to nitroalkenes in water was developed by using a rational approach, via chemometrics‐assisted 'Design of Experiments' (DoE) optimisation. This way it was possible to screen 9 different parameters, their interaction with each other, and the full chemical space, with minimum experiments in an efficient manner.